DEVELOPING COOPERATIVE LESSON PLANNING FOR TEACHING SOCIOLINGUISTIC: DIRECTNESS AND INDIRECTNESS IN COMUNICATION - Haryani, Tiara Retno (Universitas Islam Lamongan, 2016)
people communicate in various ways in order to interact and gain relationship to other people. In this era, people expand communication not onl y to people in their milieu such as famil y, but also to people from various environments which have different background culture.Keywords: cooperative, lesson planning, directness and indirectness communication